Analysis of Genetic Diversity of Indian Buffalo Breeds by DNA Markers - Sangwan, M.L. (Journal of Buffalo Science, 2012)
Buffalo is an important species contributing significantly to Indian economy. There is urgent need to study genetic diversity between and within breeds using appropriate set of microsatellite markers which can be further supplemented by using Genome sequencing data, phonemics and high density arrays. Animal resources are valuable assets of a country. Present buffalo breeds have gene pools of wide representation and valuable combination of genes. Genetic variability also provides the opportunity for tracing the history of populations, species, and their ancestors through DNA based markers. For the overall breed improvement and to meet future challenges there is an urgent need to characterize buffalo breeds. It is our responsibility to conserve, preserve and maintain the animal genetic diversity.